2020
DOI: 10.1007/s41669-020-00204-z
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analyses, Costs and Resource Use, and Health-Related Quality of Life in Patients with Follicular or Marginal Zone Lymphoma: Systematic Reviews

Abstract: Background Follicular lymphoma (FL) and marginal zone lymphoma (MZL) are types of indolent non-Hodgkin lymphoma (NHL) that develop in the B lymphocytes (also known as B cells).Objective The aim of this study was to conduct a comprehensive review of studies relating to cost effectiveness, costs and resource use, and health-related quality of life (HRQoL) in patients with FL or MZL. Methods Three separate systematic reviews were conducted to identify all published evidence on cost effectiveness, costs and resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Indeed, a recent systematic review in this area concluded a substantial need for further studies due to a significant evidence gap in this disease area [42]. This gap seems to be most prominent in previously treated FL patients, although this population appears to be particularly burdened by high health-care resource use and costs [42]. With our study we fill part of this gap, which could potentially be used as a reference point for future economic evaluations.…”
Section: Relevance Of the Studymentioning
confidence: 88%
See 1 more Smart Citation
“…Indeed, a recent systematic review in this area concluded a substantial need for further studies due to a significant evidence gap in this disease area [42]. This gap seems to be most prominent in previously treated FL patients, although this population appears to be particularly burdened by high health-care resource use and costs [42]. With our study we fill part of this gap, which could potentially be used as a reference point for future economic evaluations.…”
Section: Relevance Of the Studymentioning
confidence: 88%
“…Rituximab is in use since a couple of decades for previously treated FL patients but thus far, no formal cost-effectiveness analysis has been performed. Indeed, a recent systematic review in this area concluded a substantial need for further studies due to a significant evidence gap in this disease area [42]. This gap seems to be most prominent in previously treated FL patients, although this population appears to be particularly burdened by high health-care resource use and costs [42].…”
Section: Relevance Of the Studymentioning
confidence: 99%
“…The ICER for G + chemo compared with Ra + chemo was $28,879 per QALY gained (95% CR = $14,524-$86,968), and the ICER for G + chemo compared with Rp + chemo was $23,082 per QALY gained (95% CR = $10,861-$76,500). 23,24 Our results from the model indicate that G + chemo continues to offer good economic value, including improved patient outcomes, compared with R + chemo or equivalents based on rituximab biosimilars, and that value-based policy decisions should consider G + chemo as standard of care for patients with untreated FL. Several factors drive the value of G + chemo in our economic model.…”
Section: Tablementioning
confidence: 90%
“…Furthermore, patients requiring subsequent lines of treatment were likely to be older and have more comorbid conditions than newly diagnosed patients. Disease progression was also a major driver of HCRU, cost and health-related quality of life following relapse after initial treatment and associated with substantial economic burden [23]. Beveridge et al, in a USA study, reported a four-fold increase in annual costs and medical visits of $30,890 for progression versus $8704 for non-progression [24].…”
Section: Discussionmentioning
confidence: 99%